2022
DOI: 10.18805/lr-4630
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Effect of Water Stress on Root Traits in Green Gram Cultivars

Abstract: Background: Green gram is one of the important pulse crops of chief protein source, with ability to fix nitrogen. Erratic rainfall, while it’s grown as rainfed crop, leads to the yield loss due to water stress. Plant root system architecture is plastic and is important sink of photosynthates. In general, the ability of plants to change its root distribution for exploiting water deeper in soil profiles can be an important mechanism to avoid soil water stress. Identification of genotypes based on root traits und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Under moisture stress, TCGS-1694 showed the highest Pn (24.56 µ mol CO 2 m -2 sec -1 ), gs (0.40 mole H 2 ‚ O m²/sec), Ci (198.54 µmole CO 2 ‚ mole -1 ) and E (4.42 m. mole H 2 ‚ O m²/sec ) values, in contrast to Kadiri-6 (15.50 µ mol CO 2 m -2 sec -1 , 0.09 mole H 2 ‚ O m²/ sec, 125.63 µmole CO 2 ‚ mole -1 , 1.22 m. mole H 2 ‚ O m²/sec respectively), in which the minimum were recorded. This effect has also been reported for drought stressed cotton (EL Sabagh et al, 2020), green gram (Amarapalli, 2022) and sugarcane (Misra et al, 2020).…”
Section: Photosynthetic Parameterssupporting
confidence: 78%
“…Under moisture stress, TCGS-1694 showed the highest Pn (24.56 µ mol CO 2 m -2 sec -1 ), gs (0.40 mole H 2 ‚ O m²/sec), Ci (198.54 µmole CO 2 ‚ mole -1 ) and E (4.42 m. mole H 2 ‚ O m²/sec ) values, in contrast to Kadiri-6 (15.50 µ mol CO 2 m -2 sec -1 , 0.09 mole H 2 ‚ O m²/ sec, 125.63 µmole CO 2 ‚ mole -1 , 1.22 m. mole H 2 ‚ O m²/sec respectively), in which the minimum were recorded. This effect has also been reported for drought stressed cotton (EL Sabagh et al, 2020), green gram (Amarapalli, 2022) and sugarcane (Misra et al, 2020).…”
Section: Photosynthetic Parameterssupporting
confidence: 78%
“…Therefore, Balaka district would benefit from improved bean varieties tolerant to low soil fertility and drought. Similarly, Patel et al (202 2) and Amarapalli (2022) identified genotypes adaptable to drought stress in Cluster bean and Green gram varieties respectively.…”
Section: Bean Cropping Season and Systemmentioning
confidence: 95%
“…For the selection of drought tolerant genotypes, study on root traits related to below plant parts is essential. Among these traits, root traits (Root length density (RLD), Root dry weight (RDW), root surface area, average root diameter, root volume,) were found to be the major contributors to drought tolerance (avoidance) under rainfed condition (Uga et al, 2013, Geetha, 2022. In drought prone Southern Telangana Zone of Telangana, where recurrent droughts in July-November, 2019 is ever present restraint on maximum production of Pigeonpea, the genotypes with better root characteristics is a major research priority in order to recommend to the farmers.…”
Section: Introductionmentioning
confidence: 99%